Perspectives on the intrinsic rate of population growth. Issue 10 (16th July 2016) - Cortés, Enric
Summary: The intrinsic rate of population increase ( r max ) is a fundamental metric in ecology and evolution of immediate practical application in conservation and wildlife management. I examine the interpretation of r max by revisiting the theory behind the density‐independent and density‐dependent paradigms. The criticism that density‐independent approaches underestimate r max per se, often expressed in the field of fisheries, is shown to be theoretically unfounded. The difficulty in estimating r max is due to lack of knowledge on the depletion level of the population rather than theory. I reviewed a method commonly used to estimate extinction risk of marine and terrestrial populations and show that it has been used incorrectly. I also examined five other methods to calculate r max, the Euler–Lotka equation, and four other methods derived from it. I used the same data inputs for a suite of 65 shark populations with a broad range of life histories as an example to show that the incorrectly used extinction risk method overestimates r max . I compared the r max values for sharks obtained with the incorrectly applied extinction risk method to published values for other vertebrate taxa to further show that this method generates implausible values for this group of predators. I advocate focusing on obtaining estimates of all required vital rates simultaneously when possible while taking into consideration the exploitation history of the population under study as a pragmatic way to provide plausible estimates of r max . The Euler–Lotka equation and its derivations are recommended for different degrees of data availability, particularly for slow‐ and medium‐growing populations, to provide sensible advice for conservation and management of living vertebrates in situations where a series of credible abundance estimates are not available as is often the case in marine systems. Methods that combine allometry and demography should also be further explored.